Obstacles to organizational communication in the organization - Ketfi, djamila (Journal of Social Sciences and Humanities, 2020)
Communication is one of the most fundamental elements of human interaction, since an individual cannot live apart from others, he exchanges ideas and feelings with them to influence and be influenced by them, and thus demonstrate the need to improve communication skills in society. Studying communication and trying to understand its elements, dimensions and methods, and highlighting some of its core competencies are important and fundamental in social organizations and institutions.This type of communication is intended to be a process to transmit the necessary data and information in various directions within and outside the organizational structure so that the required communication between the different operators is facilitated.This transfer requires a range of procedures, methods, means and arrangements to ensure the production, transfer and use of data in a manner that ensures the effectiveness of the Organization. It was therefore important to develop communication methods and skills for all members of the Organization and to overcome the obstacles that could hinder its functioning by developing a clear policy that members are aware of the activities, the objectives, plans and programmes and the political, economic and social factors governing the Organization, in addition to being able to achieve communications policy objectives effectively and successfully to make the institution capable of achieving organizational effectiveness by having the capacity to grow and adapt to the environment to achieve the predetermined objectives; because the organization is actually a complex structure of communication and relationships between individuals, based on a series of decisions related to the achievement of a particular objective or set of objectives through different activities. Given the importance of organizational communication within the Organization, I have considered in this research paper the constraints of organizational communication within the Organization, explaining the concept of organizational communication, its importance, its fundamental elements, its objectives, its models and the psychological and organizational constraints that could hinder the achievement of the Organization’s objectives. I have also listed ways to overcome these problems.